1977
DOI: 10.1071/ar9770177
|View full text |Cite
|
Sign up to set email alerts
|

Water stress and phenology in wheat

Abstract: Single wheat plants (cv. Gabo) were sown in tall pots and top-watered so that growth proceeded without stress until the time of floral initiation. Having reached this stage, plants encountered increasing stress as soil water was depleted. At intervals after the dawn leaf water potential, ψ1, had reached values of –5, –10, –15 bars etc., the stress was relieved with water sufficient for unstressed development until anthesis. The anthesis dates of plants which had encountered mild stress (ψ1 down to about ndash;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
38
1
4

Year Published

1989
1989
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(50 citation statements)
references
References 0 publications
7
38
1
4
Order By: Relevance
“…However, our results are in accordance with previous reports in which flowering was generally hastened slightly by mild water stress (Fischer & Turner, 1978). In other crops like wheat, the effect of stress in flowering depends on the intensity; under mild stress flowering can be accelerated while it can be delayed under severe stress (Angus & Moncur, 1977).…”
Section: Discussionsupporting
confidence: 94%
“…However, our results are in accordance with previous reports in which flowering was generally hastened slightly by mild water stress (Fischer & Turner, 1978). In other crops like wheat, the effect of stress in flowering depends on the intensity; under mild stress flowering can be accelerated while it can be delayed under severe stress (Angus & Moncur, 1977).…”
Section: Discussionsupporting
confidence: 94%
“…Preanthesis moisture stress delayed development, whereas moisture stress during grain filling hastened development, in agreement with the result of Angus and Moncur (1977). Different mechanisms have been suggested to explain this phenomenon.…”
Section: Discussionsupporting
confidence: 77%
“…In studies by Hodges and French (1985) and Angus and Moncur (1977) water stress was reported to affect development rate of crops, and Peltonen (1993) showed that the N fertilization rate may affect development rate under controlled conditions. In contrast, Franck et al (1992) noticed no effect of N fertilization rate on duration of development phases.…”
Section: Parametrisation Of the Modelmentioning
confidence: 97%